2006
DOI: 10.1002/art.21975
|View full text |Cite
|
Sign up to set email alerts
|

A randomized controlled trial with an anti‐CCL2 (anti–monocyte chemotactic protein 1) monoclonal antibody in patients with rheumatoid arthritis

Abstract: Objective. Chemokines such as CCL2/monocyte chemotactic protein 1 (MCP-1) play a key role in leukocyte migration and are potential targets in the treatment of chronic inflammatory disorders. The objective of this study was to evaluate the effects of human anti-CCL2/MCP-1 monoclonal antibody (ABN912) treatment in patients with rheumatoid arthritis (RA).Methods. Patients with active RA were enrolled in a randomized, placebo-controlled, dose-escalation study of ABN912. Infusions were administered on day 1 and day… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
152
1
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 240 publications
(163 citation statements)
references
References 15 publications
9
152
1
1
Order By: Relevance
“…15,16 CCL2 plasma level was 10-fold higher in animals receiving blocking antibody than in untreated mice (Figure 4A), and in vitro recruitment of splenocytes by plasma of animals treated with aCCL2 compared to untreated was improved (Supplementary Fig. S4E).…”
Section: Resultsmentioning
confidence: 99%
“…15,16 CCL2 plasma level was 10-fold higher in animals receiving blocking antibody than in untreated mice (Figure 4A), and in vitro recruitment of splenocytes by plasma of animals treated with aCCL2 compared to untreated was improved (Supplementary Fig. S4E).…”
Section: Resultsmentioning
confidence: 99%
“…Apart from findings of an impaired activation-induced cell death (14), the increased number of Gr-1ϩ monocytes in the bone marrow of CCR2-deficient mice (33) might contribute to the aggravation of arthritis, provided that the leukocytes in the bone marrow have access to the inflamed joints, which appears possible in view of the extensive destruction of the bone architecture in this model. In addition, a recent clinical trial showed that blockade of the MCP-1-CCR2 interaction by a humanized antibody against MCP-1 was associated with a worsening of rheumatoid arthritis (34). Indeed, CCR2 might not be the ideal target for an antibody-mediated depletion of monocytes as a therapeutic approach in arthritis, since crosslinkage of CCR2 on basophils activates basophils to release IL-6, and activation of basophils markedly aggravates arthritis.…”
Section: Discussionmentioning
confidence: 99%
“…This was attributed to the expression of CCR2 on regulatory T cells (Tregs) in the mouse and suggests that care should be taken not to interfere with Treg trafficking in autoimmune disease. Unfortunately, the first clinical trial inhibiting the CCL2-CCR2 axis conducted on rheumatoid arthritis patients with an anti-CCL2 antibody was disappointing in that although reduction of macrophage accumulation into the joints was observed, the end-point of reduction in clinical score was not achieved [19].…”
Section: Introductionmentioning
confidence: 99%